1998
DOI: 10.1161/01.cir.98.11.1078
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Myocardial Viability in Medically Treated Patients With Global Left Ventricular Dysfunction Early After an Acute Uncomplicated Myocardial Infarction

Abstract: In medically treated patients with severe global left ventricular dysfunction early after acute uncomplicated myocardial infarction, the presence of myocardial viability identified as inotropic reserve after low-dose dobutamine is associated with a higher probability of survival. The higher the number of segments showing improvement of function, the better the impact is of myocardial viability on survival. The presence of inducible ischemia in this set of patients is the best predictor of cardiac death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(79 citation statements)
references
References 25 publications
1
75
0
3
Order By: Relevance
“…Because the prognosis of patients with subendocardial infarction is better than that with transmural infarction, assessment of the transmurality of myocardial necrosis and ischemia is an important clinical issue for patients with acute myocardial infarction or with chronic myocardial ischemia (22,27). However, it has been difficult to make a diagnosis of subendocardial infarction by two-dimensional echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…Because the prognosis of patients with subendocardial infarction is better than that with transmural infarction, assessment of the transmurality of myocardial necrosis and ischemia is an important clinical issue for patients with acute myocardial infarction or with chronic myocardial ischemia (22,27). However, it has been difficult to make a diagnosis of subendocardial infarction by two-dimensional echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] It has been shown that quantification of myocardial viability early after acute myocardial infarction provides a valuable tool for assessment of reversible myocardial LV dysfunction; moreover, the presence of substantial viable myocardium after infarction is associated with better outcome. 7 At present, sophisticated imaging modalities, including nuclear imaging (with single-photon emission computed tomography [SPECT] and positron emission tomography), dobutamine stress echocardiography, or MRI, are used for assessment of myocardial viability. 5,7 …”
mentioning
confidence: 99%
“…It has been demonstrated that individuals submitted to myocardial revascularization can exhibit absence of parietal thickness in the infarcted area, however, the same can occur during exercise or any other form of stress. This fact explains the improvement in the functional capacity of infarcted patients who are submitted to revascularization, even without any improvement in the ventricular function at rest [11].…”
Section: Myocardial Viabilitymentioning
confidence: 94%